1988
DOI: 10.1093/infdis/157.5.911
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mycoplasma pneumoniae from Children with Lower-Respiratory-Tract Infections

Abstract: The prevalence and clinical pictures of Mycoplasma pneumoniae infections among children were studied using culture and serological techniques. The isolation rate was 22% (195 of 885) in pneumonic patients and 11% (66 of 600) in non-pneumonic patients. In patients three years of age or less, M. pneumoniae was isolated at the same rate from febrile and afebrile cases and from wheezy and non-wheezy cases. In older patients, however, M. pneumoniae was frequently isolated from febrile but non-wheezy cases. A peak i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Such data contrasts with results published by various authors who point out that first infection in early infancy is usually asymptomatic and that the most affected group is that between five and nine years [1,7,10,[12][13][14]. However, Nagayama et al [15], after studying the cases diagnosed in the pediatric practice of a general hospital in Japan, show that infection occurs very frequently in small children, four being the age with the greatest number of cases registered.…”
Section: Discussionmentioning
confidence: 66%
“…Such data contrasts with results published by various authors who point out that first infection in early infancy is usually asymptomatic and that the most affected group is that between five and nine years [1,7,10,[12][13][14]. However, Nagayama et al [15], after studying the cases diagnosed in the pediatric practice of a general hospital in Japan, show that infection occurs very frequently in small children, four being the age with the greatest number of cases registered.…”
Section: Discussionmentioning
confidence: 66%
“…However, the 1:640 titer, as the single highest antibody titer, is better suited for diagnostic criteria in epidemiological studies than for direct management of individual patients. 13 This study also provided information on reinfection in children after a relatively short interval from the first MP infection. It was previously known that the IgM response may persist for months or years following infection.…”
Section: Discussionmentioning
confidence: 99%
“…A 4-fold or greater rise in the antibody titers and/or a single titer >1:640 were considered diagnostic of MP infections. 12,13 Antimycoplasma antibody titer was followed up in the following two clinical settings: clinic revisit with new symptoms suggesting respiratory tract infections (20 episodes) and planned sequential follow-up of antimycoplasma antibody titers in the patients without any respiratory symptoms at the time of follow-up (69 episodes), which was part of our previous study. 12 …”
Section: Serologymentioning
confidence: 99%
“…Instead, it stimulates macrophages via toll-like receptors to release immunomodulatory and inflammatory cytokines and chemokines such as interleukin (IL)-18 and IL-8, which cause excessive immune responses resulting in the formation of pneumonia [13,14,25,26,29]. This immunopathogenesis of pneumonia must be age dependent because it has been reported that children younger than 3 years of age less frequently develop pneumonia than older children when infected by this organism [12,21]. This holds true in this series of patients; that is, the oldest patient had the most severe disease and the youngest patient had the mildest disease.…”
Section: Discussionmentioning
confidence: 99%